Esktrak ikan haruan (Channa striata) menurunkan jumlah makrofag pada fase inflamasi proses penyembuhan luka (Extract of haruan (Channa striata) decreases macrophages count in inflammation phase of wound healing process ) - Putri Sri Hartini; Nurdiana Dewi; Lisda Hayatie (Journal of Dentomaxillofacial Science, 2015)
Haruan is a kind of freshwater fishes commonly found in South Kalimantan. Haruan extract contains nutritional substancessuch as albumin, Zn, Fe, Cu, and unsaturated fatty acid which can help accelerate wound healing. The aim of this studywas to histopathologically assess the effect of 100%, 50%, and 25%haruan extract compared to aquadest and ibuprofenon macrophages count in inflammation phase of wistar rats’ buccal mucosa wound healing. This research was a trueexperimental with post test-only with control design. Samples used were 30 wistar rats divided into 5 groups, 100%, 50%,25% haruan extract treatment groups, ibuprofen treatment group as positive control, and aquadest treatment group asnegative control. Mean macrophages counted on day 3 of 100%, 50%, 25% haruan extract treatment groups aquadest,and ibuprofenl were 2.05, 4.4, 3.9, 3.3, 2.4 respectively. In conclusion, haruan extract had a significant effect in decreasingmacrophages count in inflammation phase of wound healing.